Exchange rate sensitivity towards money supply, GDP and interest rate: a case study on Malaysian ringgit against few other currencies / Siti Zakiah Mat Som - Mat Som, Siti Zakiah (2007)
This study was conducted to find whether does exchange rate of Malaysian Ringgit against few other currencies sensitive towards money supply, GDP and interest rate. The exchange rates of Malaysian Ringgit against US Dollar, Singapore Dollar, Deutschmark and Japanese Yen have been chosen for this study. This study is emphasizes on the relationship between exchange rate of Malaysian Ringgit against few other currencies with money supply, GDP and interest rate. The objectives of this study are to know whether money supply, GDP and interest rate have influence on exchange rate of Malaysian Ringgit against few other currencies or not, and also to examine whether there are positive or negative relationship between exchange rate of Malaysian Ringgit against few other currencies with money supply, GDP and interest rate. The data were collected on monthly basis from Jan 1991 to Aug 1998 and from Jul 2005 to Sep 2006. Data were analyzed using SPSS program. From the findings, it can be concluded that money supply has an influence on exchange rate of Malaysian Ringgit against US Dollar. The findings also show that there is positive relationship between exchange rate of Malaysian Ringgit against US Dollar with money supply. For GDP and interest rate, there is no relationship with the exchange rate of Malaysian Ringgit against US Dollar. For Singapore Dollar, Deutschmark and Japanese Yen, there no significant at all with money supply, GDP and interest rate.